Qualities of reflection: using Saul's (2001) On Equilibrium to restore humanity to reflection in healthcare. Issue 5 (3rd September 2017) - Eaton, Colette
Abstract: Reflection features strongly in health and care work as a tool for personal and professional development and can support us as practitioners to be critical and self-aware in practice, of practice and the impact on clients and patients. Its power to transform learning and practice, however, has been watered down through recipe-following in reflective recording and through the avoidance of recording uncertainty or practice that might not measure against professional codes. Drawing on the humanist philosophy of John Ralston Saul, I suggest using Saul's 'six qualities' as themes for reflective questions. I reflect on the influence of reason through codes of practice and offer suggestions for questions to restore an awareness of Self in work with clients and patients. Finally, from my experience as a counselling student and healthcare educator, I argue that we should have a greater appreciation of the power of uncertainty in reflective recording.